RELEVANSI SIKAP ISTIQAMAH DENGAN KEBAHAGIAAN HIDUP MANUSIA DALAM TAFSIR AL-MARAGHI KARYA AHMAD MUSTHAFA AL-MARAGHI DAN TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB - Fa’iz Alfaris; Eni Zulaiha (Adisam Publisher, 2025)
Consistency is one of the important concepts in Islam that can help individuals achieve true happiness in life. In Tafsir Al-Maraghi and Tafsir Al-Misbah, Ahmad Musthafa Al-Maraghi and M. Quraish Shihab explain the relevance of consistency to human happiness. The purpose of this study is to analyse the relevance of steadfastness to human happiness in Tafsir Al-Maraghi and Tafsir Al-Misbah, as well as to compare the interpretations of Ahmad Musthafa Al-Maraghi and M. Quraish Shihab regarding the relevance of steadfastness to human happiness. This study uses qualitative research methodology with content analysis as the data analysis technique. The data sources for this study are Tafsir Al-Maraghi and Tafsir Al-Misbah. The results of this study indicate that the attitude of istiqamah has a very close relevance to human happiness. Ahmad Musthafa Al-Maraghi and M. Quraish Shihab explain that istiqamah is the key to achieving true happiness in life. However, there are differences in interpretation between the two regarding the relevance of the attitude of istiqamah to human happiness, especially in terms of the emphasis on the spiritual and practical aspects of istiqamah.